2023
DOI: 10.1140/epjc/s10052-023-11214-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing phase structure of strongly coupled matter with holographic entanglement measures

Abstract: We study the holographic entanglement measures such as the holographic mutual information, HMI, and the holographic entanglement of purification, EoP, in a holographic QCD model at finite temperature and zero chemical potential. This model can realize various types of phase transitions including crossover, first order and second order phase transitions. We use the HMI and EoP to probe the phase structure of this model and we find that at the critical temperature they can characterize the phase structure of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 156 publications
0
4
0
Order By: Relevance
“…Upto d = d c , connected phase is the physical whereas beyond d > d c disconnected phase is physical. Some recent works in this direction can be found in [35,52,[63][64][65][66][67][68][69][70][71][72][73]. We have depicted this fact in Fig.…”
Section: Computation Of Holographic Entanglement Entropymentioning
confidence: 79%
“…Upto d = d c , connected phase is the physical whereas beyond d > d c disconnected phase is physical. Some recent works in this direction can be found in [35,52,[63][64][65][66][67][68][69][70][71][72][73]. We have depicted this fact in Fig.…”
Section: Computation Of Holographic Entanglement Entropymentioning
confidence: 79%
“…[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. In related studies, it has been observed that the behavior of entanglement near phase boundaries can exhibit distinctive characteristics, making it a potentially effective order parameter for phase transitions [28][29][30][31][32][33]. However, the behavior of entanglement entropy, even for the same physical process, can vary significantly when different models are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the AdS/CFT duality framework allows for the calculation of entanglement properties, such as the entanglement entropy and the entanglement of purification, through the concept of minimum surface area in the bulk space [23][24][25][26][27]. Holographic QCD [28][29][30][31][32][33][34] and holographic condensed matter theory [35,36] research has found that, as non-local observables, entanglement properties can also serve as effective order parameters for various phase transitions. These include transitions such as metal-insulator phase transitions [36][37][38], superconducting phase transitions [39][40][41][42], deconfinement phase transitions [43][44][45][46][47][48][49][50], and phase transitions related to quark-gluon matter [28,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation